Magnetic critical behavior and anomalous Hall effect in 2H-Co_{0.22}TaS_{2} single crystals - Yu Liu (刘育); Zhixiang Hu (胡之翔); Eli Stavitski; Klaus Attenkofer; C. Petrovic (Physical Review Research, 2021)
We report ferromagnetism in 2H-Co_{0.22}TaS_{2} single crystals where Co atoms are intercalated in the van der Waals gap, and a systematic study of its magnetic critical behavior in the vicinity of T_{c}∼28 K. The obtained critical exponents β=0.43(2), γ=1.15(1), and δ=3.54(1) fulfill the Widom scaling relation δ=1+γ/β and follow the scaling equation. This indicates that the spin coupling in 2H-Co_{0.22}TaS_{2} is of three-dimensional Heisenberg type coupled with long-range magnetic interaction, and that the exchange interaction decays with distance as J(r)≈r^{−4.69}. 2H-Co_{0.22}TaS_{2} exhibits a weak temperature-dependent metallic behavior in resistivity and negative values of thermopower with dominant electron-type carriers, in which obvious anomalies were observed below T_{c} as well as the anomalous Hall effect (AHE). The linear scaling behavior between the modified anomalous Hall resistivity ρ_{xy}/μ_{0}H and longitudinal resistivity ρ_{xx}^{2}M/μ_{0}H implies that the origin of the AHE in 2H-Co_{0.22}TaS_{2} should be dominated by the extrinsic side-jump mechanism.